Long intergenic non-protein coding RNA 00707 regulates chondrocyte apoptosis and proliferation in osteoarthritis by serving as a sponge for microRNA-199-3p. Issue 4 (1st April 2022) - Xu, Yan; Duan, Liang; Liu, Shizhang; Yang, Yuanyuan; Qiao, Zhi; Shi, Liang
ABSTRACT: It is known that long intergenic non-protein coding RNA 00707 (LINC00707) promotes lipopolysaccharide (LPS)-injury and microRNA-199-3p (miR-199-3p) regulates chondrocyte proliferation and apoptosis. Both processes participate in osteoarthritis (OA). We predicted that LINC00707 and miR-199-3p may interact with each other. Therefore, LINC00707 and miR-199-3p may interact with each other to participate in OA. In this study, the expression of LINC00707 and miR-199-3p in both OA and normal articular cartilage tissues was analyzed using RT-qPCR. The subcellular location of LINC00707 and its direct interaction with miR-199-3p were explored by nuclear fractionation assay, RNA pull-down assay and Luciferase reporter assay, respectively. The role of LINC00707 and miR-199-3p in regulating the expression of each other was analyzed using an overexpression assay, followed by RT-qPCR. The role of LINC00707 and miR-199-3p in regulating OA chondrocyte proliferation and apoptosis was analyzed by BrdU assay and cell apoptosis assay, respectively. OA tissues exhibited increased expression of LINC00707 and decreased expression of miR-199-3p. LINC00707 directly interacted with miR-199-3p in cytoplasm. However, LINC00707 and miR-199-3p overexpression failed to affect each other's expression. LPS treatment increased LINC00707 expression and decreased miR-199-3p expression in OA chondrocyte. LINC00707 overexpression increased the apoptosis of OA chondrocytes induced by LPS and suppressed the proliferation of OA chondrocytes. Moreover, LINC00707 suppressed the role of miR-199-3p in enhancing cell proliferation and suppressing cell apoptosis. In conclusion, LINC00707 can be detected in cytoplasm and it may sponge miR-199-3p to regulate chondrocyte proliferation and apoptosis in OA. Graphical Abstract: uf0001